2019
DOI: 10.1029/2019jb017796
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Viscosity Into Classical Homogeneous Nucleation Theory for Water Bubbles in Silicate Melts: Reexamination of Bubble Number Density in Ascending Magmas

Abstract: To evaluate the effect of melt viscosity on bubble nucleation, we formulated the homogeneous nucleation rate of water bubbles to explicitly include melt viscosity. The viscosity coefficient appears in the preexponential factor of the nucleation rate in terms of the Péclet number: the ratio of the bubble growth timescale by molecular diffusion and the viscous relaxation timescale. The preexponential factor is almost constant when viscosity is low (or a high Péclet number), whereas it linearly decreases with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The higher concentration of solids provided more nucleation sites, reducing the amount of undercooling required for nucleation. However, in 1.5 wt% collagen slurries, the increased viscosity was likely to have suppressed the formation of nuclei [ 46 ]. This effect might have outweighed the effects of the presence of increased nucleation sites, shifting the nucleation events to higher degrees of undercooling.…”
Section: Discussionmentioning
confidence: 99%
“…The higher concentration of solids provided more nucleation sites, reducing the amount of undercooling required for nucleation. However, in 1.5 wt% collagen slurries, the increased viscosity was likely to have suppressed the formation of nuclei [ 46 ]. This effect might have outweighed the effects of the presence of increased nucleation sites, shifting the nucleation events to higher degrees of undercooling.…”
Section: Discussionmentioning
confidence: 99%
“…This would reduce the theoretical value of BND by an order of magnitude. Nishiwaki and Toramaru (2019) indicated that, when the viscosity of the melt is high, it suppresses nucleation. The BND in Toramaru's (1995) viscosity-controlled regime may be overestimated.…”
Section: Future Directions In Microscopic Surface Tension Researchmentioning
confidence: 99%